ANALISIS FINANSIAL PEMANFAATAN DAUN NIPAH (Nypa fruticans Wurmb.) SEBAGAI BAHAN BAKU PEMBUATAN PEMBUNGKUS ROKOK - Dian Puspita Sari; Agus Purwoko; Kansih Sri Hartini (Program studi Kehutanan USU, 2013)
Nypa is one of the non-timber forest product. Almost all parts of the nypa plant can be used, one of which is its leaves. Nypa leaves can be used as raw material of cigarette wrapping as a substitute of cigarette paper for curl up the tobacco. This study aims to find out of processing nypa leaves into cigarette wrapping, the financial feasibility, and the contribution of business to labor incomes at UD. Metro Jaya, Pekubuan village, Tanjungpura Sub-district, Langkat District. The research was conducted in June-July 2012. The sample was selected by purpossive sampling. The method using cost and revenue analysis, RC ratio analysis, break event point analysis, payback period analysis, and contribution to labour income. The processing of nypa leaves make it do the traditional system. The results showed that financially, the business of processing nypa leaves into cigarette wrapping was feasible, because its RC ratio more than one (1.44). BEP of production volume is 695 kg and BEP of price is about Rp. 17,250,- per kilogram. While the payback period is 8.03 and the contribution value from the business of cigarette wrapping to labor income is almost 100%. Keywords : nypa leaves, cigarette wrapping, financial analysis, contribution to income.